Comparison of the RLS and LMS Algorithms to Remove Power Line Interference Noise from ECG Signal - Noor K. Muhsin (Al-Khwarizmi College of Engineering – University of Baghdad, 2010)
Biomedical signal such as ECG is extremely important in the diagnosis of patients and is commonly recorded with a noise. Many different kinds of noise exist in biomedical environment such as Power Line Interference Noise (PLIN). Adaptive filtering is selected to contend with these defects, the adaptive filters can adjust the filter coefficient with the given filter order. The objectives of this paper are: first an application of the Least Mean Square (LMS) algorithm, Second is an application of the Recursive Least Square (RLS) algorithm to remove the PLIN. The LMS and RLS algorithms of the adaptive filter were proposed to adapt the filter order and the filter coefficients simultaneously, the performance of existing LMS algorithm of the adaptive filters cause completely removing of the PLIN comparing with the RLS algorithm that reducing the noise level only.